A Long Time Coming: Delays in Collective Apologies and Their Effects on Sincerity and Forgiveness. Issue 3 (21st April 2017) - Wenzel, Michael; Lawrence‐Wood, Ellie; Okimoto, Tyler G.; Hornsey, Matthew J.
Abstract : Political apologies by one group to another often occur a significant period of time after the original transgression. What effect does such a delay have on perceptions of sincerity and forgiveness? A delayed apology could reflect the offender group's reluctance to apologize, or, alternatively, it could represent time and consideration spent on developing an appropriate response. In the latter case, the delayed apology would represent a sincere acknowledgment of the harm done, whereas in the former case it would not. In two studies, we found that a verbal collective apology, when delayed, was perceived to be less sincere than when offered more immediately following a transgression, and this translated to less forgiveness. However, in Study 2, the negative effects of time delay on sincerity and forgiveness were mitigated or reversed when the apology was in the form of commemoration. The commemorative apology, in particular when delayed, gave rise to favorable attributions (including representativeness of apologizing group, commitment to remember, and giving voice to victims), which mediated the effects on sincerity. The results suggest that collective apologies that are offered with considerable delay appear less meaningful and less deserving of a forgiving response, unless the apologizing group is able to express consideration and thoughtfulness through the apology process.